RANCANG BANGUN SISTEM RACK IN DAN RACK OUT PMT OTOMATIS DI KUBIKEL 20 KV BERBASIS ARDUINO MEGA 2560 MENGGUNAKAN VTSCADA 11.2 - Puteri, Ratna Azizah; Subari, Arkhan; Tadeus, Dista Yoel (Gema Teknologi, 2020)
The 20 KV PMT (Circuit Breaker) is an important equipment for the reliability of electricity distribution. Therefore it must be maintained so that it is always in good condition with regular maintenance. Prior to maintenance, PMT is terminated from the bus bar, which is called the rack out process. After maintenance, the PMT is reconnected with the bus bar, which is called the rack in process. Usually, 20 KV PMT rack in and rack out process in maintenance or disturbance is still using the manual method. The 20 KV PMT can only be racked in and racked out in one way, by turning the lever. The lever will rotate the bolt as a PMT rail. In the manual method, there is no system for monitoring the condition of the bus bar whether it is has electric-voltage or not. There is also no remote control that can rack in and rack out. So officers must ensure the conditions of PMT and bus bars are safe manually, before maintenance is carried out. This is quite troublesome and dangerous for officers. From these problems, in this research Â designed a system that could ensure the condition of the PMT and the bus bar was safe before the rack in and rack out process was carried out and could monitor and control the system remotely using SCADA. Rack-in and rack-out automation system using VT SCADA, using Ethernet Shield that has been connected with Arduino Mega. Ethernet is connected to a mini PC. The microcontroller pins will be connected to the relays that will turn or stop the motor. The rack in and rack out commands from VT SCADA will determine the rotation of the motor so that the PMT moves. The current sensor reads the current flow and detects interference. Interference detection will automatically make PMT Rack out. System testing shows that the process of racking out in a state of maintenance or disturbance can be carried out automatically controlled by VT SCADA. Current sensor works to detect the current flowing, so that it can detect PMT interference and perform automatic rack out. The rack-in process is also capable of being remotely controlled with VT SCADA. This makes it easier for officers to also become additional reliability of PMT in the 20 KV cubicle.